ECONOMIC POTENTIAL ANALYSIS IN MALAKA REGENCY, EAST NUSA TENGGARA PROVINCE - Achmad Nur Sutikno (Jurnal Ilmu Pemerintahan Widya Praja, 2025)
Malaka Regency, East Nusa Tenggara Province is a newly formed region with various potential natural and human resources that have not been optimally developed. It has a type A Motamisin Cross-Border Post (PLBN), which is an official post that functions to support cross-border trade between countries. The purpose of this study is to analyze the economic structure, its shifts, and determine business field categories to increase economic growth in the border region. Using a quantitative descriptive design with the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share (SS) methods, and analyzing the relative position of business field categories. The final result is that there are 7 leading sectors or basic sectors. The results of the economic growth analysis (shift share) show that the primary sector category is Agriculture/Forestry/Fisheries, which grew by 5.93 percent, contributing 102,315.45 billion rupiah or 37.88 percent to the GRDP. The secondary sector, namely the construction sector, contributed 42.78 billion rupiah or 15.84 percent to the GRDP. The tertiary sector, namely transportation/warehousing, accounted for 24.43 billion rupiah, or 9.05 percent. Based on the classification of business sector development, eight sectors are categorized as having rapid growth, five as having potential (prospective), and four as developing. Social distancing due to the COVID-19 pandemic has impacted the movement and growth of the economy in Malaka Regency.